Wall stress determines systolic and diastolic function — Characteristics of heart failure. (1st January 2016) - Alter, Peter; Koczulla, A. Rembert; Nell, Christoph; Figiel, Jens H.; Vogelmeier, Claus F.; Rominger, Marga B.
Abstract: Introduction: Heart failure can be caused by systolic or diastolic dysfunction. Diagnosing diastolic dysfunction remains challenging, although several criteria have been identified. Ventricular wall stress is crucially involved. It is hypothesized whether increased end-diastolic and end-systolic ventricular wall stress as assessed by the wall stress index is associated with cardiac dysfunction and thus provide novel diagnostic criteria. Methods: 1050 consecutive patients with suspected non-ischemic heart failure covering a broad spectrum from normal to severely impaired cardiac function were observed. Cardiac magnetic resonance imaging was performed to assess left ventricular (LV) volumes, myocardial mass, peak ejection (PER) and filling rate (PFR). Results: A reduced PFR was found in 348 patients (33.1%), which resulted from 275 of 422 patients (65.2%) with reduced and from 73 of 628 patients (11.6%) with preserved LVEF (p < 0.0001). Increased LV volume and mass was correlated with reduced PER and PFR (p < 0.0001). Increased end-diastolic wall stress was the strongest predictor of a reduced PER (OR 4.5 [2.6 to 7.8], p < 0.0001) and increased end-systolic wall stress predicted a reduced PFR (OR 1.2 [1.1 to 1.3], p < 0.0001). Increased end-systolic wall stress was correlated with increased pulmonary pressure (p < 0.0001). Normal end-systolic wall stress < 18 kPa had a favorable predictive value for the absence of an impaired filling and increased pulmonary capillary pressure. Conclusion: Increased end-diastolic wall stress precedes a reduced ventricular ejection rate and increased end-systolic wall stress determines an impaired diastolic filling. It is thus suggested to add assessment of ventricular wall stress as diagnostic criterion of heart failure.